Experimental and numerical assessment of water-based photovoltaic/thermal collectors with varied tubular absorber cross-sections - Shirin Rostami; Adnan Ibrahim; Amir Aziat Ishak; Ahmad Fazlizan; Ahmad Fudholi; Kamaruzzaman Sopian; Alireza Dehghani-Sanij; Amin Shahsavar; Khaled M. Al-Aribe (Case Studies in Thermal Engineering)
This study aims to develop 3D numerical models utilizing COMSOL software to analyze the heat transfer (HT) behaviour of water-based photovoltaic/thermal (WPV/T) collectors with circular, and elliptical tubular cross-sections with different dimensions to find an optimized and efficient PV/T design. Indoor experimental tests were conducted to validate the numerical results. The performance of PV/T was evaluated in terms of governing parameters, including the mass flow rate (m˙), solar irradiance (I), heat gain, maximum power (Pmax), Reynolds number (Re), thermal (ηth) and electrical (ηel) efficiency, the temperature difference between the outlet and inlet water (To-Ti), the average cell temperature, and total efficiency (ηtotal). It was determined that m˙=0.04 kg/s was the optimal water flow rate for the best performance. The results indicate that the PV/T collector with the elliptical cross-section tube with the least hydraulic diameter achieved the maximum total efficiency, both numerically and experimentally, at 76.9 % and 72.94 %, respectively, under turbulent flow conditions with Re=5502.92 and I = 1000 W/m2. ηtotal of the elliptical PV/T collectors is approximately 10 % and 6 % higher than that of circular design, respectively at the optimum flow rate, and I = 1000 W/m2. It is also found that tubes with lower hydraulic diameter values, while maintaining the same tube cross-section perimeter, exhibit higher HT characteristics compared to those with greater hydraulic diameters. The findings from this innovative and comprehensive study indicate an opportunity to enhance the HT properties of the PV/T system by optimizing the cross-sectional design and hydraulic diameter of the absorber tube, ultimately increasing total efficiency. Additionally, the optimized design opens avenues for future research and can be further developed for both industrial and domestic applications.